Strategic R&D alliance factors that impact innovation success in the biotechnology industry. (1st January 2012) - Kim, Kelly Y.
This paper examined the impact of strategic R&D alliances on biomedical product innovation by small biotechnology firms in the USA. Inferential statistics involving logistic regression modelling was applied to analyse the influence of different types of collaborators on innovation success. The results showed that for start-up companies, an increase in the number of corporate partners was both positively and significantly associated with the firms' innovation success, as measured by successful product development to the commercialisation stage, but such relationship did not hold for older firms. Moreover, an increase in the number of alliances with universities had no statistically significant association with an improvement in the innovation performance of start-ups nor of older firms. These findings may help inform alliance management by technology managers as they assess and balance the composition of their network of R&D partners to optimise their strategic benefit.